Novel enhancements of cyclotron based production, purification & applications of the PET radionuclide copper-61: Complexation to nanospheres for biomedical imaging - Asad, Ali Haidar Kasim (Curtin University, 2016)
For thirty years, cyclotron-produced radioisotopes have attracted considerable interest in biomedicine. This thesis describes novel contributions to the production and purification of the positron-emission-tomography (PET) radioisotope copper-61, and its complexation to several bifunctional chelators. Using these technologies we determined the biodistributions of silica nanospheres (Si-NS) in a small-animal model. Si-NS are a promising nanoplatform for delivering diagnostic and therapeutic targeting agents at tumour-cellular level. This research has demonstrated significant potential for PET-radiometal radiophannaceuticals in theranostics.